GRANULITE-FACIES METAMORPHIC CONDITIONS IN THE EASTERN SØR RONDANE MOUNTAINS, EAST ANTARCTICA - アサミ, マサオ; マキモト, ヒロシ; ASAMI, Masao; MAKIMOTO, Hiroshi (National Institute of Polar Research, 1991)
P(論文) Granulite-facies metamorphism in the eastern Sør Rondane Mountains is indicated by the mineral assemblages orthopyroxene+clinopyroxene±garnet in quartz-bearing acid to basic rocks and corundum+garnet+sillimanite+spinel in quartz-free pelitic rocks. The former two-pyroxene assemblages are found almost all over the area except the northwestern nunataks Vesthjelmen, Austhjelmen, Hettene and Sørhjelmen. Nearly uniform equilibrium temperatures 780-800℃ were obtained for two-pyroxene pairs in seven gneissic rock samples extensively collected from the area, being consistent with the two-pyroxene temperatures 780℃ and 760℃ reported from the northwestern nunatak, Austhamaren, and the central part, Balchenfjella, respectively (GREW et al. : Proc. NIPR Symp. Antarct. Geosci., 3,124,1989; MAKIMOTO et al. : Proc. NIPR Symp. Antarct. Geosci., 4,18,1990). A garnet-bearing rock, from Balchenfjella, of the seven samples gave garnet-clinopyroxene temperatures and pressures of 750-790℃ and 7-8kb, and garnet-orthopyroxene temperatures 750-770℃. Despite the difference of structural trends between the northwestern and the principal parts of this area, these T-P values, together with the occurrence of kyanite relics in both parts, suggest that actually all of the area suffered the same, medium pressure-type, prograde regional metamorphism attaining to the granulitefacies conditions. departmental bulletin paper